Osteoporosis-Related Randomized Clinical Trials With Middle-Aged and Older Adults Registered on the International Clinical Trials Registry Platform - Lai, Fenghua; Pei, Ling; Chen, Xinwen; Li, Jin (Frontiers in Endocrinology, 2021)
Background A better understanding of the current features of osteoporosis-related randomized clinical trials (RCTs) is important for improving clinical trial designs and promoting the translatability of results into benefits for patients. Therefore, this study aimed to investigate the characteristics of registered RCTs on osteoporosis among middle-aged and older adults on the International Clinical Trials Registry Platform (ICTRP). Methods Osteoporosis-related RCTs registered on the ICTRP were searched on December 31, 2020. The main features of eligible RCTs were assessed. We searched PubMed, Google scholar, Medline, and Embase databases for the publication status of completed RCTs. Results A total of 537 osteoporosis-related RCTs were identified for analysis. The number of registered RCTs increased rapidly in 2005 (N = 47). Of these, 346 (64.4%) RCTs involved only women and 275 (51.2%) were retrospectively registered. Most RCTs were of open-label design (61.3%). The most common primary purpose of osteoporosis-related RCTs was treatment (72.3%). Intervention investigated was mainly focused on medication (62.8%), followed by lifestyle or education (19.0%), and dietary supplement (10.4%). After trial completion, the results of only 140 (35.5%) RCTs were available on the ICTRP, and the publication rate after trial completion was 30.5%. Conclusions RCTs on osteoporosis among middle-aged and older adults were dominated by retrospectively registered and open-label trials. Most trials lacked available results and associated publications. More awareness of prospective registration and blinding design in osteoporosis-related RCTs is needed. Further, publication and dissemination of RCTs results should be promoted.